Synthesis of silver nanoparticles using various reducing agents and stabilizers - Lutpillaeva, Masuda; Xoshimov, Farhod; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The results of a series of experiments on the synthesis of silver-based nanoparticles are presented and a new method for their preparation is proposed. Silver nitrate salt was used as the basis of the nanoparticles. During the synthesis process, various reducing agents (glucose, sodium citrate, hydrazine) and stabilizers of the resulting nanoparticles (protein solutions of albumin and gelatin) were used. Some samples of silver nanoparticles were obtained without the participation of reducing agents. Preliminary conclusions have been made about the influence of individual synthesis parameters on the stability of silver nanoparticle systems and the relationship between the degree of dispersion of nanoparticles and the color intensity of their solutions.